2018
DOI: 10.1111/liv.13979
|View full text |Cite
|
Sign up to set email alerts
|

Circulating markers of gut barrier function associated with disease severity in primary sclerosing cholangitis

Abstract: Background & Aims One important hypothesis in primary sclerosing cholangitis pathophysiology suggests that bacterial products from an inflamed leaky gut lead to biliary inflammation. We aimed to investigate whether circulating markers of bacterial translocation were associated with survival in a Norwegian primary sclerosing cholangitis cohort. Methods Serum levels of zonulin, intestinal fatty acid binding protein, soluble CD14, lipopolysaccharide and lipopolysaccharide‐binding protein were measured in 166 prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…Antibiotic treatment has been recently confirmed to be effective in improving serological markers of cholestasis in PSC patients, with a possible indirect effect via modifications of the gut microbiome [61]. Moreover, a number of markers of bacterial translocation and gut barrier dysfunction (i.e., zonulin, intestinal fatty acid binding protein, soluble CD14, LPS and LPS-binding protein, antibodies against F-actin and gliadin, and various anti-microbial antibodies) have been found elevated in the sera of PSC patients, with a positive correlation with progressive disease [62,63]. Interestingly, genome-wide association studies have revealed a common risk factor for PSC and Crohn's disease in the fucosyltransferase 2 (FUT2) locus, which influences fecal and bile bacterial composition and has recently been linked to the development of hepatobiliary abnormalities in mice [64,65].…”
Section: Figurementioning
confidence: 99%
“…Antibiotic treatment has been recently confirmed to be effective in improving serological markers of cholestasis in PSC patients, with a possible indirect effect via modifications of the gut microbiome [61]. Moreover, a number of markers of bacterial translocation and gut barrier dysfunction (i.e., zonulin, intestinal fatty acid binding protein, soluble CD14, LPS and LPS-binding protein, antibodies against F-actin and gliadin, and various anti-microbial antibodies) have been found elevated in the sera of PSC patients, with a positive correlation with progressive disease [62,63]. Interestingly, genome-wide association studies have revealed a common risk factor for PSC and Crohn's disease in the fucosyltransferase 2 (FUT2) locus, which influences fecal and bile bacterial composition and has recently been linked to the development of hepatobiliary abnormalities in mice [64,65].…”
Section: Figurementioning
confidence: 99%
“…The gut microbial metabolism involve a wide range of molecules ranging from short‐chain fatty acids and vitamins to secondary bile acids and neurotransmitters . Blood from the gut enters the systemic circulation through the liver via the portal vein, meaning that the liver is at the centre of gut microbiome‐host interaction . Microbiota‐derived molecules have the potential to activate the immune system and trigger inflammation, providing the liver with the challenging task of balancing tolerance to beneficial and unharmful molecules and metabolites with the need to act as a firewall against pathogens and harmful microbe‐derived molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Blood from the gut enters the systemic circulation through the liver via the portal vein, meaning that the liver is at the centre of gut microbiome‐host interaction . Microbiota‐derived molecules have the potential to activate the immune system and trigger inflammation, providing the liver with the challenging task of balancing tolerance to beneficial and unharmful molecules and metabolites with the need to act as a firewall against pathogens and harmful microbe‐derived molecules . Disturbances of the gut‐liver axis are therefore potentially the key players in several liver diseases, and maybe biliary diseases especially as the gut microbiome is central to bile acid homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, gut leakage of pro-inflammatory bacterial products (e.g. lipopolysaccharides, LPS) also contributes by involving innate immune responses [32][33][34][35]. Furthermore, a series of studies now strongly indicate that the gut microbiota may be involved in PSC pathogenesis [17,[36][37][38][39][40] giving rise to clinical trials involving fecal transplantation, non-absorbable antibiotics, and other means of manipulating the gut microbiome in patients [17,[41][42][43].…”
Section: Pathophysiological Basis Of Therapymentioning
confidence: 99%
“…Novel and more specific biomarkers of liver fibrosis, discriminating collagen formation from degradation as opposed to just reflecting the more static fibrosis load, have also been associated with clinical outcome in PSC and may be suited to evaluate treatment effects, with PRO-C3 the currently most promising single marker [193]. Markers of inflammation, autoimmunity or gut barrier function including IL-8 [194], VAP-1 [177], autotaxin [195] or soluble CD14 [33] have also demonstrated association with clinical outcome and may represent relevant surrogate endpoints in trials targeting these pathways; however, independent validation and more knowledge about the natural history and fluctuations of theses markers, alone and in combination, are warranted.…”
Section: Costly Time-consumingmentioning
confidence: 99%